2010
DOI: 10.1118/1.3515457
|View full text |Cite
|
Sign up to set email alerts
|

Telerobotic system concept for real‐time soft‐tissue imaging during radiotherapy beam delivery

Abstract: Remotely controlled robotic U.S. imaging is feasible in the radiotherapy environment and for the first time may offer real-time volumetric soft-tissue guidance concurrent with radiotherapy delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…This is of particular importance not only for treatment systems with longer system latencies but also with the realization of more complex image-guided radiotherapy systems under development that are subject to larger system latencies. [26][27][28][29] RMSE for diaphragm respiratory prediction was higher than abdominal wall respiratory prediction RMSE. This is potentially due to the lower sampling rate of diaphragm respiratory data (5 Hz) compared to abdominal wall respiratory data (30 Hz); a previous study by Ren et al found that a lower sampling rate resulted in a reduction in prediction accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…This is of particular importance not only for treatment systems with longer system latencies but also with the realization of more complex image-guided radiotherapy systems under development that are subject to larger system latencies. [26][27][28][29] RMSE for diaphragm respiratory prediction was higher than abdominal wall respiratory prediction RMSE. This is potentially due to the lower sampling rate of diaphragm respiratory data (5 Hz) compared to abdominal wall respiratory data (30 Hz); a previous study by Ren et al found that a lower sampling rate resulted in a reduction in prediction accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…Two telerobotic systems for US monitoring of radiotherapy were developed by Schlosser et al (2010Schlosser et al ( , 2011 at Stanford University, with the latter being commercialized by SoniTrack Systems (Palo Alto, CA, USA). Another telerobotic research system for US monitoring of radiotherapy was developed at Lubeck University by Kuhlemann (2013) and has been tested on the hearts of healthy human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In addition, the radiation therapy LINAC does not affect speckle tracking algorithms, 13 while commercially-available optical tracking systems may be used to relate speckle tracking coordinates to the treatment room coordinate system. 14,15 For subtle probe adjustments that may be required during treatment, a haptic teleoperated robotic system was introduced by Schlosser et al 16 with minimal treatment plan modifications required to accommodate the robot and US probe. Wu et al 17 additionally demonstrated that the presence of the US probe for transabdominal imaging minimally affects radiotherapy treatment plans when the anterior-posterior treatment beam is omitted.…”
Section: Introductionmentioning
confidence: 99%